COVID-19 and regional shifts in Swiss retail payments - Sébastien Kraenzlin; Christoph Meyer; Thomas Nellen (Swiss Journal of Economics and Statistics, 2020)
This paper analyzes card payments to the retail sector in Switzerland during the COVID-19 crisis. We provide evidence on aggregate effects and regional shifts. Pronounced shifts-which persisted post-lockdown-can be observed from urban to suburban and rural areas and among cantons. Data allow us to identify directly two sources of shifts: "tourists and business travelers" and "e-commerce." We indirectly identify additional sources: infection risk, lockdown measures, working from home, shopping tourism, and cash substitution. The COVID-19 crisis seems to have reinforced pre-existing trends that may have faster than anticipated effects on the economy. Our analysis underscores the usefulness of real-time card payment data to inform policymakers.
Keywords: E21; E42; E65; E71; R10; 330; COVID-19; Lockdown; Card payment data; Regional sale shifts